Synthesis and fabrication of nanocomposite magnesia doped barium strontium titanate for thick film humidity sensor - Farahani, Hamid Barzabadi (2013)
Water vapour is a highly interactive matter around the earth glob. Accordingly,monitoring and control of the surrounded humidity is extremely demanded in different areas, i.e., domestic and industrial applications. By virtue of the indispensable demands in such fields, moisture sensing technology has rapidly progressed to overcome the drawbacks. Thick film technology has been discerned as a convenient technology from the last decades which exhibits high integration,design flexibility, affordable cost and material intermingled design. A provskite family of compound ceramics with the chemical formula of ABX3, are natural minerals in nature. The scope of this dissertation research is to fabricate and configure of miniaturized double layer thick film humidity sensors which is realized based on the nanocomposite sensing elements. The humidity sensitive properties of nano aggregates were examined in view point of their potential applications for humid sensors. BaTiO3 and SrTiO3 provskites were proposed as precursors. To examine the microstructure and improve the moisture-sensitive behaviour of the (Ba0.5,Sr0.5)TiO3 compound, the MgO admixtures were added with 1,3 and 5mol% concentration. Nano-powders were mixed based on molar ratio and prepared via conventional solid state reaction. The thick film inks were prepared by mixing appropriate ratio of an organic vehicle and heat treated nanocomposites, and screen printed onto an alumina substrate utilizing DEK-J1202RS automatic machine. The surface morphology and electrical properties of the nano grains and developed thick film specimens were studied. The performance characteristics of the proposed prototype ceramic and sensors (BST, BSTM1, BSTM3, and BSTM5) were evaluated and analyzed by means of Impedance Analyzer and LCR meter with respond to 20%-95% RH through laboratory humidity simulation chamber, and frequency variations in range of 20Hz to 2MHz. The validation of the sensors analytical model is illustrated and processed using experimental outcomes. The novel contributions of this research are contained of two major parts. First, the characterizations have shown that all the four different compounds met the criteria to be used as humidity sensing elements. Addition of admixtures has led to particle size diminution (~ 2nm per concentration). Second, the results from the DC and AC analysis have shown that all the sensors are operating based on the ionic-conduction mechanism, and applicable for being dual functional. The structural outcomes of the films have revealed that the grains had matured by dopant additions (~ 5nm per doping value), and highly contributed in transduction process. Overall, the BSTM3 has shown to be the most promising compound to be used as a thick film humidity sensor.